Assessment of Information Technology Governance Maturity Using COBIT 5: A Case Study in the Retail Sector - Fenny Lestari; A. Haidar Mirza (Journal of Renewable Energy and Smart Device, 2026)
This study evaluates the capability level of information technology (IT) governance for the ASSIST application in a retail company using the COBIT 5 framework. Unlike previous studies that focused on limited governance domains, this research provides a holistic evaluation covering governance, planning, implementation, service management, and performance monitoring processes to identify governance capability gaps and formulate strategic improvement priorities. A qualitative case study approach was employed through interviews, observations, and documentation analysis involving key organizational stakeholders. The assessment was conducted using the COBIT 5 capability model to measure current and expected governance capability levels. The results show that all evaluated domains achieved maturity scores above 86.00%. The average current maturity score reached 87.98%, while the expected capability level averaged 92.82%, resulting in an overall gap of 4.84%. All domains achieved Capability Level 5, showing that governance processes are well established and continuously improved. The largest gap was identified in the EDM domain, showing the need to strengthen executive oversight and strategic governance practices. These findings demonstrate that the ASSIST application is supported by a mature IT governance environment that aligns information technology with business objectives, enhances operational efficiency, supports service continuity, and provides practical guidance for governance optimization in the retail sector.